Analysis of the Effectiveness of Using Problem Based Learning (PBL) Model in Social Studies Learning in Elementary School: A Systematic Literature Review - Novita Sari; Elizar; Sumarno (Universitas Pendidikan Ganesha, 2025)
The Problem-Based Learning (PBL) model is a teaching method that focuses on solving real-life problems to enhance students’ engagement and understanding in the learning process. In elementary social studies learning, PBL is implemented to develop students’ critical thinking, analytical, and collaborative skills. This study aims to evaluate the effectiveness of the PBL model in elementary social studies learning using a Systematic Literature Review (SLR) approach. The SLR method was employed to collect and analyze relevant studies published between 2019 and 2024. From 101,000 articles identified, nine key studies were screened and analyzed in depth through the stages of identification, screening, eligibility, inclusion, and data synthesis. The findings reveal that implementing the PBL model in social studies learning significantly improves students’ conceptual understanding, motivation, learning outcomes, and critical thinking skills. Moreover, this model encourages active participation and helps students comprehend social studies concepts in more authentic contexts. The results imply the need for systematic integration of PBL in elementary social studies learning to foster active engagement and higher-order thinking skills. Teachers are encouraged to enhance their competence in designing contextual problem-based scenarios, while policymakers should support professional development related to innovative learning models such as PBL. Furthermore, this study provides a foundation for future research exploring the effectiveness of PBL in developing students’ 21st-century skills and social character.